2016
DOI: 10.1080/02786826.2016.1216072
|View full text |Cite
|
Sign up to set email alerts
|

Deagglomeration testing of airborne nanoparticle agglomerates: Stability analysis under varied aerodynamic shear and relative humidity conditions

Abstract: 2016) Deagglomeration testing of airborne nanoparticle agglomerates: Stability analysis under varied aerodynamic shear and relative humidity conditions, ABSTRACTOccupational exposure to nanomaterial aerosols poses potential health risks to workers at nanotechnology workplaces. Understanding the mechanical stability of airborne nanoparticle agglomerates under varied mechanical forces and environmental conditions is important for estimating their emission potential and the released particle size distributions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Charge buildup alone probably does not suffice (Leck & Bigg, 2010). Shear forces require air velocities on the order of 100 m s −1 to measurably break up accumulation mode agglomerates (Ding et al., 2016). Steric repulsion of nanoparticles with polysaccharide chains and electrostatic repulsion of negative functional groups (typical in marine gels) can hinder aggregation in dispersions (Adroher‐Benítez et al., 2017; Bachhar & Bandyopadhyaya, 2016; Moncho‐Jordá, 2013).…”
Section: Possible Aitken Mode Formation Mechanisms In the Eventmentioning
confidence: 99%
“…Charge buildup alone probably does not suffice (Leck & Bigg, 2010). Shear forces require air velocities on the order of 100 m s −1 to measurably break up accumulation mode agglomerates (Ding et al., 2016). Steric repulsion of nanoparticles with polysaccharide chains and electrostatic repulsion of negative functional groups (typical in marine gels) can hinder aggregation in dispersions (Adroher‐Benítez et al., 2017; Bachhar & Bandyopadhyaya, 2016; Moncho‐Jordá, 2013).…”
Section: Possible Aitken Mode Formation Mechanisms In the Eventmentioning
confidence: 99%
“…In this context, other intercomparison studies on PNSD measurements by SMPS were performed on TiO 2 (Leskinen et al, 2012;Ding et al, 2016). Babick et al, (2016a,b) showed for several nano-additived materials that the SMPS number-weighted median diameters deviate from electron microscopy results by a factor not larger than 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out by Piccino et al (2012), surveyed companies' estimates on production of various nanomaterials and found that most companies estimated a median of 5500 tons/year of nanosilica and 550 tonnes/year of nanoalumina were produced within Europe. The introduction of these materials into the workplace institutes conceivable health risks and toxicity when human exposure is concerned (Ding et al 2016;Njuguna et al 2009).…”
Section: Introductionmentioning
confidence: 99%